2000
DOI: 10.1042/bj3500599
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rat liver malonyl-CoA decarboxylase and the study of its role in regulating fatty acid metabolism

Abstract: In the liver, malonyl-CoA is central to many cellular processes, including both fatty acid biosynthesis and oxidation. MalonylCoA decarboxylase (MCD) is involved in the control of cellular malonyl-CoA levels, and functions to decarboxylate malonylCoA to acetyl-CoA. MCD may play an essential role in regulating energy utilization in the liver by regulating malonyl-CoA levels in response to various nutritional or pathological states. The purpose of the present study was to investigate the role of liver MCD in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 29 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…The intermediate species (50-51 kDa) was found only in mitochondria and peroxisomes and the lowest Mw species (48-49 kDa) was present exclusively in the peroxisomes. Other laboratories [25,26] using adenovirally expressed or transfected MCD, have reported the presence of different MCD species; but to our knowledge, this is the first time that the existence of different MCD species and their organelle specificity has been observed in untransfected tissue. Whether the different molecular weight species reflect transcriptionally or post-transcriptionally generated isoforms or proteolytic modification of the enzyme remains to be established.…”
Section: Discussionmentioning
confidence: 65%
“…The intermediate species (50-51 kDa) was found only in mitochondria and peroxisomes and the lowest Mw species (48-49 kDa) was present exclusively in the peroxisomes. Other laboratories [25,26] using adenovirally expressed or transfected MCD, have reported the presence of different MCD species; but to our knowledge, this is the first time that the existence of different MCD species and their organelle specificity has been observed in untransfected tissue. Whether the different molecular weight species reflect transcriptionally or post-transcriptionally generated isoforms or proteolytic modification of the enzyme remains to be established.…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, it has been strongly suggested that an increase in MCD activity can be the factor contributing to a decrease in malonyl-CoA and increase in fattyacid oxidation in muscle tissue [34]. Moreover, the activity of MCD is highest in tissues such as heart and liver, which are known as the major organs of fatty-acid oxidation [35]. Also, in pathophysiological states such as diabetes or hyperlipidaemia, where lipid metabolism is altered, MCD has an important role in the regulation of fatty-acid metabolism [36].…”
Section: Discussionmentioning
confidence: 99%
“…MCD was originally identified in the uropygial gland of the goose [11]. We also showed MCD to be highly expressed in mammalian cardiac muscle [12], and provided evidence to suggest that cardiac MCD plays an important role in regulating fatty acid metabolism in the heart [10,13]. Regulation of MCD occurs both at the level of transcription and post‐translation [14,15].…”
mentioning
confidence: 95%